Analisis Produktivitas Alat Berat Proyek Pembangunan Jalur Ganda Kereta Api - Siti Choiriyah Choiriyah; M.Ferdaus Noor Aulady Aulady; Felicia Tria Nuciferani; Diah Listyaningsih Listyaningsih; Alfani Subhan Subhan (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2024)
The mojokerto - along double railroad construction project certainly requires a good and strong and ideal subgrade, so that in the process of work required soil reinforcement work. The heavy equipment used is excavator, excabreaker, dump truck, and vibrator roller. This study aims to determine the productivity and cost of heavy equipment working in the field. The occurrence of delays in the rail piling work makes this work exceed the planned time limit. The method used in this research is a quantitative method, namely by collecting the required data. To overcome the delay, the addition of heavy equipment is analyzed with a choice of 4 options. Based on the analysis, the best option is to use 2 excabreaker units at a cost of Rp 191,089. 940.00 on rail piling work because it is more effective and efficient. The results of the analysis based on the productivity of heavy equipment working in the field, soil reinforcement work can be completed within 25 days and a total cost of Rp 732,746,726.00. Thus the soil reinforcement work can be completed in accordance with the planned time.